If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1 + -1x) = 10 (1 * 5 + -1x * 5) = 10 (5 + -5x) = 10 Solving 5 + -5x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -5x = 10 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = 10 + -5 -5x = 10 + -5 Combine like terms: 10 + -5 = 5 -5x = 5 Divide each side by '-5'. x = -1 Simplifying x = -1
| 6x-7=4x+12 | | 8=4e^2x+1 | | 10+10y=20 | | 33-2x=9-8x | | 7+6x=-35 | | x-y-3=o | | 5(3-4x)=35 | | 3xy+2x+4y+2xy+3x+y= | | 1260-288x+12x^2=0 | | 8x+9x-15=25+17-2x | | 8-3[5-(8y-4)]= | | -6(p-8)=96 | | x(2)-2x-15=-12 | | x(2)-2x-15=-20 | | Solvew+(-2)=-18 | | 2/3k=4 | | x(2)-2x-15=0 | | 2x+3y+4x-1y= | | z^2-16+30i=0 | | x(2)-25=-25 | | x(2)-25=-16 | | x(2)-25=-1 | | 3x+6=(3x+2) | | 2(6n-8)=4+7n | | -22+18-(-17)= | | 0.2-0.02(x+3)=0.02(1-x) | | 2x^2+9x=2x+49 | | x(2)+4x-5=-10 | | x(2)+4x-5=-9 | | -0.5c=2.5 | | x(2)+4x-5=0 | | x(2)-9=-8 |